Enhanced nutritionally induced adipose tissue development in mice with stromelysin-1 gene inactivation - Maquoi, Erik; Demeulemeester, Diego; Vörös, Gabor; Collen, Désire; Lijnen, H. Roger (Thrombosis and Haemostasis, 2003)
To investigate a potential role of stromelysin-1 (MMP-3) in development of adipose tissue, 5 week old male MMP-3 deficient mice (MMP-3-/-) and wild-type (MMP-3+/+) controls were kept on a high fat diet (HFD) for 15 weeks. MMP-3-/- mice were hyperphagic and gained more weight than the MMP-3+/+ mice. At the time of sacrifice, the body weight of the MMP-3-/- mice was significantly higher than that of the MMP-3+/+ mice, as was the weight of the isolated subcutaneous (SC) and gonadal (GON) fat deposits. Significant adipocyte hypertrophy was observed in the GON but not in the SC adipose tissue of MMP-3-/- mice. Fasting plasma glucose and cholesterol levels were comparable in both genotypes, whereas triglyceride levels were significantly lower in MMP-3-/- mice. Staining with an endothelial cell specific lectin revealed a significantly higher blood vessel density and larger total stained area in the GON adipose tissues of MMP-3-/- mice. Thus, in a murine model of nutritionally induced obesity, MMP-3 impairs adipose tissue development, possibly by affecting food intake and/or adipose tissue-related angiogenesis.Theme paper: Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: MMP-3; stromelysin-1; obesity; adipose tissue; adipocyte; angio-genesis